2014
DOI: 10.7448/ias.17.4.19691
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of late presenters in Bucharest

Abstract: IntroductionLate presentation is associated with increased healthcare costs, rates of HIV transmission and poor outcome. In Romania, in 2012, one third of individuals with new HIV diagnosis were late presenters (LP).ObjectiveThe aim of the study was to evaluate the epidemiological and clinical characteristics associated with late presentation.MethodsWe retrospectively studied patients over 18 years old, notified in our institution between January 2012 and December 2013, including 499 out of 727 newly diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In our study, late presentation and advanced HIV disease were more frequent among patients entering care in the older age groups, female patients, those who were heterosexually infected and IDUs. Reports from Romania and Denmark are consistent with our observation that a significantly higher proportion of heterosexual patients, compared with the MSM group, are late presenters . In our study, the odds of late care entry and advanced HIV disease increased consistently with age.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, late presentation and advanced HIV disease were more frequent among patients entering care in the older age groups, female patients, those who were heterosexually infected and IDUs. Reports from Romania and Denmark are consistent with our observation that a significantly higher proportion of heterosexual patients, compared with the MSM group, are late presenters . In our study, the odds of late care entry and advanced HIV disease increased consistently with age.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies showed that males were more likely to present late in HIV diagnosis 25 26 , while some other studies presented no significant difference between males and females in late HIV diagnosis 27 28 . These conflicting reports are reflective of the difference in health-seeking behaviors and HIV testing policies, as well as the heterogeneity of the parameters used among the different studies.…”
mentioning
confidence: 82%
“…The reason is that the screening campaigns that were carried out targeted mainly young people and offered very little opportunities for old people to be screened early. The reason was that old people were perceived to be at lower risks of being HIV-positive, but they were often infected when they were young and the diagnosis was not made [21]. Moreover, practitioners performed HIV screening for young people than elders when they are hospitalized.…”
Section: Factors Associated With Late Presentationmentioning
confidence: 99%